2017
DOI: 10.1590/2359-3997000000185
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle intervention using the psychoeducational approach is associated with greater cardiometabolic benefits and retention of individuals with worse health status

Abstract: Objective: This study aimed to compare the effects of two lifestyle intervention programs for type 2 diabetes mellitus (T2DM) prevention -traditional or interdisciplinary psychoeducationbased intervention -in daily habits and cardiometabolic risk factors and investigate the role of the psychoeducational approach for the retention of individuals in the program. Subjects and methods: Between 2008 and 2010, in a public health service, 183 pre-diabetic individuals were allocated to two 18-month interventions invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(31 reference statements)
3
2
0
Order By: Relevance
“…The results of this study are consistent with some past research which showed that adherence to an intense lifestyle intervention is lower for patients with depression (18). Previous research has shown the effectiveness of pharmacotherapy (i.e., metformin) for diabetes prevention (19).…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study are consistent with some past research which showed that adherence to an intense lifestyle intervention is lower for patients with depression (18). Previous research has shown the effectiveness of pharmacotherapy (i.e., metformin) for diabetes prevention (19).…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, this is in line with other studies which found that different interventions (lifestyle, psychoeducation, exercise) are of limited effectiveness when it comes to antipsychotic-induced weight gain or metabolic changes over a longer time period (e.g., 18-months of antipsychotic-treatment) ( 19 , 20 ). This is also in line with the results of our previous study performed at the ZUHC, where we found no effects of the PsyLOG m-health intervention compared to TAUin preventing antipsychotic-induced weight gain and metabolic changes over 6 months follow-up ( 22 ).…”
Section: Discussionsupporting
confidence: 85%
“…However, acknowledging the effect of metabolic abnormalities on morbidity, more focused strategies to counteract these side effects are needed. While several interventions involving exercise proved to be efficient over a shorter period, this effect is lost over a longer period ( 19 , 20 ). As the negative effects of metabolic abnormalities became apparent over time, it is crucial to sustain the effects of these interventions, possibly with a combination with psychosocial or behavioral interventions focused on sustaining motivation to exercise or regular supervision of exercise over a longer period ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these sessions, other sessions implemented in the G-CBT, such as the homework assignment "daily life events" and psychoeducation also help participants to be more aware of themselves and their everyday experiences in life, and broaden their perspectives to be able to feel gratitude (Peterson & Seligman, 2004). This is consistent with research conducted by Cezaretto et al (2017)) which states that psychoeducation can sustain efforts to manage psychiatric disorders with a reduced number of relapses and higher levels of function. Psychoeducation is also known to improve the quality of life of individuals.…”
Section: Discussionsupporting
confidence: 72%
“…A dysfunctional family is a condition where a family does not function correctly. This condition makes family members unable to meet their basic needs and can cause many unpleasant experiences (Chang et al, 2019;Guo et al, 2018;Jamiolkowski, 1998;Nie et al, 2019;Pagani et al, 2008). Adult individuals who were raised in dysfunctional families grew in fear due to pain and recurring trauma as a result of the actions, behavior, or words of their parents (Ubaidi, 2017).…”
mentioning
confidence: 99%